1998
DOI: 10.1111/j.1469-7793.1998.283by.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dopamine on lung liquid production by in vitro lungs from fetal guinea‐pigs

Abstract: During gestation, fetal lungs produce large quantities of fluid which contribute substantially to the amniotic fluid, particularly in the guinea-pig, where production rates appear to be higher than those for urine (Strang, 1991;Perks et al. 1992). This production is based on a Na¤-K¤-2Cl¦ cotransport system, probably located in type II cells (Strang, 1991). However, at birth it is vital for this process to be replaced by fluid reabsorption, and it is generally agreed that this is brought about by an amiloride-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In isolated adult rat lungs, SCH 23390, but neither S(-) sulpiride nor propranolol inhibited DAs effect suggesting the D1 DA receptor pathway is involved (29). In contrast, increased lung liquid absorption was mediated through D2 receptors in fetal guinea pig lung after a short-term exposure to DA (ϳ1 h) (10). Our experiments showing that the DAinduced increase in Isc can be blocked with D1/D2 receptor blockers are consistent with these reports.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In isolated adult rat lungs, SCH 23390, but neither S(-) sulpiride nor propranolol inhibited DAs effect suggesting the D1 DA receptor pathway is involved (29). In contrast, increased lung liquid absorption was mediated through D2 receptors in fetal guinea pig lung after a short-term exposure to DA (ϳ1 h) (10). Our experiments showing that the DAinduced increase in Isc can be blocked with D1/D2 receptor blockers are consistent with these reports.…”
Section: Discussionsupporting
confidence: 82%
“…Studies in isolated adult rat lungs have demonstrated that DA stimulates lung fluid absorption (10,29). However, there is some controversy regarding the specific mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limited access we presume is a result of only the smaller molecules of the population being capable of entering the matrix pores. In other studies, larger objects (2,000kDa dextrans, R S = ~27nm; and type-5 adenovirus vectors, R S = ~49nm) were shown to pass through the lens capsule in a two chamber diffusion system (62) or after anterior chamber injection (63,64). Considering the maximum pore size we have measured in the capsule, this contradiction may suggest that the capsules used in the previous reports were compromised.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, previous experiments in ATII (33) have demonstrated that they do not contribute to net transepithelial Na ϩ transport. Two studies have reported that dopamine-induced lung fluid clearance is amiloride insensitive (4,9), but a more recent study suggests a role of dopamine in ENaC regulation (18). The CNGC Na ϩ -permeant ion channel has been reported to be expressed within the lung and to be relatively insensitive to amiloride (12).…”
Section: Discussionmentioning
confidence: 97%